Assessing Efficiency and Productivity of Micro and Small Industries: An Empirical Study in North Kalimantan - ARIANI; charitin Devi; Sulistya Rini Pratiwi; Yohanna Thresia Nainggolan; Wong Sing yun (Jurnal Ekonomi Kuantitatif Terapan, 2025)
The economic statistics of the micro and small industries in North Kalimantan Province indicate that the added value reached IDR. 516.6 billion from micro industries and IDR. 46.6 billion from small industries in 2022. However, these industries only absorbed 2% of the total workforce in North Kalimantan Province. This indirectly suggests that the performance of the manufacturing sector for micro and small industries has not yet been optimized. This study aims to identify the factors influencing efficiency and assess productivity in micro and small industries in North Kalimantan Province from 2015 to 2023. The results show that only input value and output value significantly affect the efficiency of micro and small industries in North Kalimantan Province, while the number of firms and the workforce do not have a significant impact on efficiency during the 2015–2023 period. However, simultaneously, input value, output value, number of firms, and workforce influence the efficiency of micro and small industries in North Kalimantan Province.